«CLASS OF EVIDENCE IIB» FOR ACUTE HEART FAILURE: WHEN, WHO, WHY? - A. M. Namitokov; F. R. Achmiz; A. S. Shimko; E. S. Dumanyan; A. A. Skopets; P. V. Sukhoruchkin; O. A. Pozdnyakova; E. D. Kosmacheva; V. A. Porhanov (Инновационная медицина Кубани)
Despite a high level of standartization of principal approaches for acute coronary syndrome treatment, in acute cardiac care department there often occur cases when therapy is not to be included in present recommendations as they are non-effective and impossible for application. Myocardial infarction is one of those situations especially when it is complicated by cardiogenic shock and ventricular arrhythmia. For overwhelming majority of ‘standard’ situations we apply recommendations with a high level of evidence I or IIa. Below we present a clinical case of treatment for acute coronary syndrome with ST-segment elevation, when non-routine used recommendations with class of evidence IIb were of great importance.